When Pandemic Interferes with Work: Psychological Capital and Mental Health of Social Workers during COVID-19. - Ho, Henry C Y; Chui, On Sang; Chan, Ying Chuen (Social Work, 2022)
The impact of the COVID-19 pandemic is not only limited to physical health but also extends to various aspects of everyday life. The present study proposes that the prolonged pandemic can lead to pandemic–work conflict (PWC). The article examines how the pandemic interferes with work, the association between PWC and mental health, and the underlying mechanism of this process. A total of 303 full-time social workers in Hong Kong responded to measures on PWC, psychological capital (PsyCap), and anxiety and depressive symptoms. Data were collected between February and April 2020, when the COVID-19 outbreak was beginning to worsen; 15.8 percent and 14.9 percent of the participants reported mild to severe anxiety and depression, respectively. Time-based PWC was positively associated and strain-based PWC was negatively associated with PsyCap, which was in turn negatively associated with anxiety and depressive symptoms. PsyCap was a significant mediator of these relationships. The findings suggest that the relationship between strain-based PWC and psychological distress can be explained by PsyCap, whereby the depletion of psychological resources may contribute to anxiety and depressive symptoms. Positive psychological resources may be an intervening point for promoting mental health among the social services workforce.